Characterization of phase change material systems using a thermal test device. Issue 12 (December 2015) - Jordà, Xavier; Esarte, Jesús; Perpiñà, Xavier; Vellvehi, Miquel; Argandoña, Gorka; Aresti, Maite
Abstract: This work presents a thermal characterization approach for phase change materials thermal management systems (PCM-TMS) based on a thermal test device (TTD) allowing simultaneous dissipation and chip temperature measurement. The tests are oriented towards PCM-TMS characterization for their application in the power electronics domain, providing an insight to the physical phenomena involved in PCM systems. The PCM-TMS used in this work consists in a 35 mm diameter and 9.5 mm height Cu case, containing a 20 ppi porous Cu mesh and a 31 °C melting temperature paraffin. It has been demonstrated that the proposed characterization methodology is suitable for the assessment of this kind of non-linear systems, allowing an easy acquisition of both, heating and cooling transients.